Job satisfaction of selected faculty members in a private university in Manila: basis for faculty enhancement program - Garcia, Dulce Dacanay (Manila : National University, 2012)
The study focused on four important dimension: salary and fringe benefits, working conditions, supervision and professional growth.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Normative-Descriptive Design.
Includes bibliographical references.